Complete denture rehabilitation in a patient with flabby ridge using an open-Window impression technique and double-spacer custom tray: A case report - Richard Austeen Halim; Taufik Sumarsongko; Rasmi Rikmasari (Indonesia Prosthodontic Association, 2026)
ABSTRACT Background: A flabby ridge is an area of mobile soft tissue found superficially, which affects both maxillary and mandibular alveolar ridges. It is a common finding in long term denture wearers, where the rate of bone resorption is very fast leading to development of hyperplastic soft tissue over the alveolar bone. These mobile, hyperplastic tissues compromise denture stability and retention, leading to patient discomfort and functional limitations. A precise impression is essential for ensuring the stability of complete dentures with flabby ridge. The fundamental principle for impressions of a flabby ridges is to apply minimal pressure on the flabby area to prevent distortion impression outcome. To achieve that, open-window technique and double spacer custom tray along with selective pressure impression techniques was employed. Objectives: This case report aims to gain impression with minimum pressure on flabby ridge to enhance retention, support, and stability of the complete denture. Case Report: A 63-year-old male patient came to the Department of Prosthodontics, Padjadjaran University, complaining that his old 10-years-used denture felt loose and uncomfortable. Intraoral examination showed that both maxillary and mandibular arches were fully edentulous, with flabby ridges present. Following the assessment, it was decided to make a new complete denture using double spacer custom tray and open-window impression techniques. Conclusion: Double spacer custom tray and open-window impression techniques helped in recording flabby tissue with minimal displacement and hence enhanced the stability, support, and retention of the denture. Keywords: Flabby Ridge, Complete Denture, Impression Techniques, Double Spacer Custom Tray, Open-Window Technique